سیرت النبی ﷺ پر فلپ ہٹی اور بروکلمان کی بعض افتراء پردازیوں کا تنقیدی جائزہ: Critical Review of Some Fabrications by Philip Hitti and Brockelmann on the Prophet's Seerah (PBUH) - Dr. irfan Saghir; Sara Javed (MEI, 2024)
In this article, the opinions and thoughts of two big names of Orientalist historians namely: Philip K. Hitti and Carl Brockelmann have been discussed which they have written in their two books namely: "History of the Islamic people"(Carl Brockelmann) and ", History of the Arabs"(Philip K. Hitti) have been described with reference to the biography of the Prophet. Basically, in these two books, the historical events from the period of Jahiliyyah in the Abbasid era of Islamic history have been discussed. Among which the biography of the Prophet, the era of the Caliphs and the Abbasid era are the most prominent. But in the article under review, only the accusations made in the Prophet's biography have been critically evaluated. The reason for choosing these two books in particular is that they are more popular in Muslim circles, these books are common in general libraries, they are given importance as teaching in madrasahs and educational institutions. It is considered necessary to examine the fact that the pioneers of Oriental thought, who are considered among the most important historians, did not adopt the scientific and research method in describing Islamic history. What are the reasons? Because of which both of them have made a sinister attempt to discredit the Prophet's biography? If these books are not critically evaluated, it is quite possible that the Muslim Ummah will begin to understand that the contents of these books regarding Islamic history, especially the Prophet's biography, are absolutely correct. Among the objections raised by both of them on the Prophet's biography, the main ones are the marriages of Hazrat Muhammad PBUH, the wrong interpretation of the Quranic verses, the doubts about the prophethood of Muhammad, the accusation that Islam is a copy of other religions, Such accusations are at the top. While describing the accusations of both of them respectively, this method has been adopted that first the opinion of each Orientalist has been explained from his book and then in the light of Qur'an and Sunnah, historical facts and some other fair Orientalists. A critical review is presented to determine the scholarly value of these views. After critically examining all the accusations and slanders, it has come to the conclusion that these two great names of Orientalists have acted fraudulently and fraudulently in describing Islamic history. No one has bothered to check what has been said in the exegetical traditions and books of Arabic literature to come up with a scholarly research and correct opinion. Both have given evidence of political enmity, bigotry and malice against Islam which can be estimated from the details described in the article. Keywords: Philip K. Hitti , Carl Brockelmann , History of the Arabs , History of the Islamic people , Orientalism , Islamic History , Prophet's biography.